Reframing Nusyuz in Islamic Family Law: A Maqasid-Based Reading of Ibn Asyur on Quran 4:34 and 4:128 - Arni, Jani; Nasution, Syamruddin; Ma’ali, Dasman Yahya; Jamaluddin, Jamaluddin; Chandra, Agus Firdaus (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2025)
This article examines the Quranic concept of nusyuz through Ibn Asyur’s al Tahrir wa al Tanwir and develops a maqasid oriented account for addressing marital conflict in contemporary Muslim families. The study adopts a qualitative library based method that closely reads Q 4.34 and Q 4.128 and triangulates classical fiqh writings thematic exegesis and recent scholarship on family law. The analysis shows that nusyuz is a relational breach that may be committed by either spouse and that Ibn Asyur proposes a gradual and ethically constrained sequence that begins with counsel then proceeds to separation of beds and only allows corrective action that must remain symbolic and non violent while prioritizing mediation whenever harm is likely. Reading the two verses together yields a symmetrical framework that protects dignity prevents harm and restores rights by aligning procedural steps with the objectives of justice compassion and public welfare. The article concludes that this maqasid based synthesis offers a text faithful and context sensitive basis for counseling adjudication and policy in Islamic family law and it recommends empirical evaluation in courts counseling services and community mediation to assess feasibility safeguards and effectiveness.